PENGARUH JUMLAH KATALIS DAN TEMPERATUR PADA PRODUKSI BAHAN BAKAR CAIR DARI BAN BEKAS DENGAN METODE PERENGKAHAN KATALITIK - Eldwita, Kinia; Lestari, Suci Dwi; Effendy A, Sahrul; ., Fatria (Politeknik Negeri Sriwijaya, 2020)
Production of the domestic tyre industries in 2019 reached 150,2 million units. With a five-year lifespan for car tire and two-year lifespan for motorcycle tire, it is estimated that millions of used tires are waste and have the potential to damage the environment. Therefore some effort is needed to recycle and convert used tyres to be more useful product. Pyrolysis (catalytic cracking), that is thermal treatment method, can degrade polystyrene which is the constituent material of tyres back into hyrocarbon compounds. This research was conducted to see the effect of temperature and catalyst percentage on liquid fuel that have obtained by using two type of catalysts. From this study it is known that entire samples meet SNI 8220:2017 for diesel fuel 48 where the sample with - Al2O3 catalyst at a temperature of 350 °C gives the best result with density of 0.83204 gram/cm3, viscosity of 3.41908 cSt, and flash point of 62 °C.